Penyaringan Informasi Dalam Pengambilan Keputusan Di Kantor Tata Ruang Kota Makassar - Munawir Gay Munawir Nawir; Sri Yuyun; Masyhadiah Diah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Indonesia Timur, 2019)
ABSTRACT This Study aims to review infromation filtering system, explain the procec of decision making, and find out the factors that support infromation filtering in the process of the decision making. The research was conducted as a case study at the office of Spatial Planning and Building Service, Makassar. The data were colected through observations, interviews docomentation, and library research, and were analysed by using the qualitative analysis with the spradly model, analysis of domain and tasxonomi to describe the result of the study. The result several that information filtering is used in making decisions, estabilishing policies, and conducting internal and extenal activities at the Office of Spatial Planning and Building Services, Makassar, Information filtering is also used as a besic referance in making decisions and developing regulations. Communication accure in meetings, and information is given in reports and reutine information channel. Futhermore, the factor that support the information filtering system are : availability of data information, the open process information filtering in making decisions, good knowledge about the scope of the problem, responsibility for assigned tasks, and communication in the organisation (internal and external) and all working units.Key Word: Information Filtering